KONVERSI SATUAN UKURAN RUMAH TANGGA KE DALAM SATUAN BERAT (GRAM) PADA BEBERAPA JENIS PANGAN SUMBER PROTEIN - Setyo Puji Handayati; Amini Nasoetion; Dadang Sukandar (Jurnal Gizi dan Pangan, 2008)
The objective of this research was to complete the information of household measurement from varies food groups in Household Measurement List (DURT). This research conducted on November 2005 – May 2006 in West Java (Bogor and Sukabumi), Central Java (Purwokerto) and Jakarta. The foods were chosen from the market with simple random sampling. There were 354 foods weighed 5 times for each food.Only 270 foods listed in Food Composition List (DKBM) that had household measurement conversion and 354 foods had not. The household measurement conversion values from some foods were consistent but the others were not consistent. It implied that the larger the physical measurement (length, width, height and thickness), the heavier the food. The inconsistency from the measurements implied that the changes of any physical measurement were not followed by the changes of weight and volume.